2021
DOI: 10.1097/im9.0000000000000052
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lockdown Measures and Meteorological Parameters on the COVID-19 Incidence and Mortality Rate in Bangladesh

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has become a public health crisis and a global catastrophe for human societies. In the absence of a vaccine, non-pharmaceutical interventions have been implemented across the world to reduce COVID-19 transmission. Recently, several studies have articulated the influence of meteorological parameters on COVID-19 infections in several countries. The purpose of this study was to investigate the effect of lockdown measures and meteorological parameters on COVID-19 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…From the COVID-19 confirmed cases data, a severe second wave is detected in Bangladesh from late March to early April 2021 ( Fig. 1 A) as compared to the first wave of April to August 2020( Imran et al, 2021 ). The exploratory analysis on Bangladeshi genomic sequences reveals a high prevalence of B.1.351 variants could be a major determining factor for the second wave of COVID-19 in the country, which is consistent with an already published study( Saha et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the COVID-19 confirmed cases data, a severe second wave is detected in Bangladesh from late March to early April 2021 ( Fig. 1 A) as compared to the first wave of April to August 2020( Imran et al, 2021 ). The exploratory analysis on Bangladeshi genomic sequences reveals a high prevalence of B.1.351 variants could be a major determining factor for the second wave of COVID-19 in the country, which is consistent with an already published study( Saha et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the identification of SARS-CoV-2, it has rapidly spread to 220 countries and territories including Bangladesh ( https://www.worldometers.info/coronavirus ), posing an unprecedented public health threat with over 165 million recorded cases of COVID-19, and more than 3.4 million deaths attributable to the disease worldwide as of May 20, 2021 ( Dong et al, 2020 ). Bangladesh documented its first case of COVID-19 on March 8, 2020 ( Imran et al, 2021 ). Since then, there have been 786,698 confirmed cases of the disease in the country, as well as 12,310 deaths with 1.56% case fatality rate (CFR) ( Dong et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…From the COVID-19 confirmed cases data, a severe second wave is detected in Bangladesh from late March to early April 2021 ( Fig. 1A ) as compared to the first wave of April to August 2020 7 . The exploratory analysis on Bangladeshi genomic sequences reveals a high prevalence of B.1.351 variants could be a major determining factor for the second wave of COVID-19 in the country, which is consistent with an already published study 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Since the identification of SARS-CoV-2, it has rapidly spread to 220 countries and territories including Bangladesh to date (https://www.worldometers.info/coronavirus), posing an unprecedented public health threat with over 165 million recorded cases of COVID-19, and more than 3.4 million deaths attributable to the disease worldwide as of May 20, 2021 6 . Bangladesh documented its first case of COVID-19 on March 8, 2020 7 . Since then, there have been 786,698 confirmed cases of the disease in the country, as well as 12,310 deaths with 1.56% case fatality rate (CFR) 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the aforementioned traditional research perspective, IMD has published several papers offering an interesting constructive perspective on early warning and surveillance of the COVID-19 outbreak. Imran et al 6 investigated the impact of lockdown measures and meteorological parameters on the COVID-19 incidence and mortality in Bangladesh. A linear regression analysis revealed that all the studied meteorological parameters were positively correlated with the daily new cases and deaths in Bangladesh, while the highest correlations were observed with the meteorological parameters 14 days prior, likely as a result of the COVID-19 incubation period.…”
mentioning
confidence: 99%